INTEL i3 3220 Microprocessor for a Complete PC Experience - Vaqui, Khan; Shaikh, Shakila (International Journal of Computer Sciences and Engineering, 2019)
The advancement of microprocessor architecture depends upon the changing phases of technology. As complexity and speed increases, memory and program performance become progressively important in defining architecture of microprocessors. Architectures and implementations that cover these limits are vibrant to the continued evolution of the microprocessor. This paper illustrates a total in depth review of the Intel manufactured i3 core 3220 microprocessor (Intel core i3). All of the features, limitations, power, application and drawbacks are discussed in his paper. Also, an attempt to cover all the aspects a Microprocessor should possess in order to work in pace with today’s world has been displayed. The Introduction has basic information of Intel core i3 3220. Related work displays basic literature for the reviews we have studied. A block diagram of basic functioning of intel core i3 Microprocessor is given. A table with precise features of Intel core i3 Microprocessor is been provided too.